The Effect of Digital Literacy, Gadget Use, And Availability of Technological Media in School on Junior High School Students’ Learning Motivation - Rindrayani, Sulastri Rini; Lely Widyawati, Lely; Dirgantoro, Ajar (Sumber Belajar Sejahtera, 2025)
This study aimed to examine the effect of digital literacy, gadget use, and availability of technological media on students’ learning motivation. This study employed stratified proportional random sampling involving 253 students of SMPN 1 Tanggunggunung Tulungagung. Data collection was conducted through a questionnaire using a Likert Scale. Data analysis utilized multiple linear regression. The results of partial hypothesis testing (t-test) indicated that digital literacy, gadget use, and availability of technological media each have a positive and significant partial effect on students' learning motivation. Simultaneously, digital literacy, gadgets use, and the availability of technological media demonstrated a significant positive effect on students' learning motivation. The contribution of the three independent variables to the dependent variable was 83.2%, while the remaining 17% was explained by other variables not explained in this study. The research results prove that students' digital literacy skills, supported by the gadget use for accessing learning resources and the availability of technological media in schools as learning resources, can increase students' learning motivation.